Syphilitic hepatitis mimicking autoimmune liver diseases - a narrative review - Merc, Artur; Łozowski, Jan; Szymański, Łukasz; Białas, Julia; Piątek, Przemysław; Paluchowska, Joanna; Gołąbek, Natalia; Mordarska, Milena; Kodura, Alicja; Piwowarczyk, Alicja (Quality in Sport, 2026)
Background: Syphilis, often referred to as the "great imitator," is a re-emerging systemic infection caused by the spirochete Treponema pallidum. In its secondary stage, it can manifest as syphilitic hepatitis (SH), a rare condition that frequently presents with a cholestatic or mixed pattern of liver injury. Due to complex immunological mechanisms, including molecular mimicry and polyclonal B-cell activation, SH can induce false-positive autoantibodies, allowing it to closely mimic autoimmune liver diseases such as primary biliary cholangitis (PBC) and autoimmune hepatitis (AIH). Aim: This narrative review aims to analyze the clinical, serological, and histopathological overlap between syphilitic hepatitis and autoimmune liver diseases, highlighting the diagnostic challenges and evaluating the potential of T. pallidum to act as an environmental trigger for true, irreversible AIH. Results: SH can perfectly mimic PBC through severe cholestasis and cross-reactivity leading to false-positive AMA results. Similarly, it can mimic AIH by presenting with marked transaminitis and false-positive ANA and ASMA. Histologically, SH is highly heterogeneous and can show interface hepatitis or neutrophilic cholangitis, while direct spirochete detection via biopsy is frequently negative due to rapid Kupffer cell phagocytosis. Crucially, while antibiotic therapy typically resolves the pathogen-induced serological mimicry, empirical immunosuppression without antibiotic coverage can lead to catastrophic dissemination, such as fulminant syphilitic retinitis and neurosyphilis. Furthermore, emerging evidence suggests that the immunological disruption caused by SH, including molecular mimicry and regulatory T-cell manipulation, can permanently break self-tolerance, triggering true AIH in genetically susceptible individuals even after successful spirochete eradication.